Superoxide-producing thermostable associate between NADPH containing lipoprotein andNADPH oxidase from rats bone marrow cells, nucleus and mitochondria membranes: isolation, purification and properties - Simonyan, R. M.; Babayan, M. A.; Simonyan, G. M.; Feschyan, S. M.; Simonyan, M. A. (Հայաստանի ԳԱԱ «Գիտություն» հրատ.)
From white rats bone marrow (BM) mitochondria, nucleus and cells membranes the isoforms of superoxide (О2)-producing thermostable associate between NADPH containing lipoprotein (NLP) and total fraction of isoform of NADPH oxidase (Nox) – (NLP-Nox), were isolated and purificated for the first time. By the expense of own NADPH the separated NLP from associates of BM NLP-Nox, only reducing (antioxidant) effect was indicated. The isoforms of these NLP were stimulate the О2-producing activity of the immune cells (leukocytes and erythrocytes) membranes Nox also, by forming the hybrid associates between these Nox (NLP-hNox).. After incubation in boiling water during 10-15 min bone marrow associates practically are not decreased its superoxide producing activities. Thus, the isoforms of О2-producing thermostable NLP-Nox associates are a new structural-functional components of the bone marrow cells, nucleus and mitochondria membranes and produced О2.by immediately mechanism in liquid and gas phases. Առաջին անգամ սպիտակ առնետի ոսկրածուծի (ՈԾ) միտոքոնդրիումների, կորիզների ու բջիջների թաղանթներից անջատվել և մաքրվել է սուպերօքսիդ (О2)-գեներացնող ջերմակայուն ասոցիատ՝ կազմված ՆԱԴՖՀ-պարունակող լիպոպրոտեինից (ՆԼՊ) և ՆԱԴՖՀ օքսիդազի իզոձևերի գումարային ֆրակցիայից (Nox)՝ ՆԼՊ-Nox: Շնորհիվ սեփական ՆԱԴՖՀ-ի՝ ասոցիատներից տարանջատված ՆԼՊ-ի իզոձևերը ցուցաբերում են միայն վերականգնիչ (հակա-օքսիդանտային) ազդեցություն: Այս ՆԼՊ-ի իզոձևերը խթանում են իմունային բջիջների (լեյկոցիտներ, էրիթրոցիտներ) թաղանթների Nox-երի О2-գեներացման ակտիվությունը՝ կազմելով այդ Nox-երի հետ հիբրիդային ասոցիատներ (ՆԼՊ-hNox): Ոսկրածուծի ասոցիատների О2-գեներացնելու ակտիվությունը չի նվազում դրանք եռացող ջրում 10-15 րոպե ինկուբացնելուց հետո: Այսպիսով, ոսկրածուծի բջիջների, կորիզների և միտոքոնդրիումների թաղանթների О2-գեներացնող ջերմակայուն ՆԼՊ-Nox ասոցիատի իզոձևերը հանդիսանում են այդ թաղանթների նոր կառուցվածքային-ֆունկցիոնալ բաղադրամասեր են և գեներացնում են О2-եր անմիջական մեխանիզմով հեղուկ և գազ ֆազերում: Впервые из мембран клеток, ядер и митохондрий костного мозга (КМ) белых крыс выделены и очищены изоформы термостабильного ассоциата между НАДФH содержащим липопротеином (НЛП) и суммарной фракции терминальных изоформ НАДФH оксидазы (Nox) – НЛП-Nox. За счет собственного НАДФH, отделенный НЛП из этих ассоциатов НЛП-Nox оказывает только восстановительный (антиоксидантный) эффект. Изоформы этих НЛП стимулируют О2-продуцирующую активность Nox мембран иммунных клеток (лейкоцитов и эритроцитов), создавая с ними гибридный ассоциат (НЛП-гNox). Ассоциаты КМ не дезактивируются после их инкубации в кипяченой воде в течение 10-15 мин. Таким образом, изоформы О2-продуцирующих термостабильных ассоциатов КМ являются новыми структурно-функциональными компонентами мембран клеток, митохондрий и ядер КМ и продуцируют О2непосредственным механизмом в жидкой и газовой фазах.
Keywords: Biochemistry